APPLICATION OF GROUP COUNSELING SERVICES EXPRESSIVE WRITING THERAPY TECHNIQUES TO REDUCE SELF INJURY BEHAVIOR OF CLASS VII STUDENTS AT SMP NEGERI 2 BANGOREJO: PENERAPAN LAYANAN KONSELING KELOMPOK TEKNIK EXPRESSIVE WRITING THERAPY UNTUK MENGURANGI PERILAKU SELF INJURY SISWA KELAS VII DI SMP NEGERI 2 BANGOREJO - Refy Ratrina Afif; Ahmad Sulthoni, M.Pd; Fajar Wahyu Prasetyo, M.Pd (Program Studi Bimbingan dan Konseling, 2024)
Cases related to cutting hands or self injury often occur in junior high school students. Self injury behavior is currently carried out by children because they still can't control their emotions well, and see on social media, following the trend that is currently happening, so from one child to invite another friend to do it. This study uses a pre-exsperimental pre-experiment approach with one – group pretest – posttest design. This study uses purposive sampling with nonprobability sampling techniques. The sample was taken from 6 students out of a total population of 41 students who were taken with a very high category of self-injury behavior. The data collection methods used are: observation, interviews, questionnaires (questionnaires), and documentation. The researcher used a data analysis technique with SPSS (statistical program for social sciences test) version 25 with the help of data tabulation through excel 2021. With prerequisite tests, analysis of normality tests, homogeneity tests and hypothesis tests. The normality test of the normality test is 0.200, the significance value is more than 0.05, namely 0.164 > 0.05 and the hypothesis test (Test – t) the significance value is less than 0.05, namely 0.000 < 0.05, then Ha is accepted and Ho is rejected. Overall, it can be concluded that in this study, the application of group counseling services of exspressive writing techniques can reduce self-injury behavior of grade VII students at SMP Negeri 2 Bangorejo.